Efektivitas Pemberdayaan pada Penyandang Disabilitas oleh Binaan Dekranasda Gowa Kecamatan Bontolempangan - A. Octamaya Tenri Awaru; Dwi Sartika; Jelsita Banna; Rahma; Nurul Muhlisah; Astrid Wahyuni (Jurnal Simki Economic, 2021)
Persons with Disabilities are people who experience physical, intellectual, mental or sensory limitations for a long period of time. This study aims to find out how the form of empowerment carried out by the Gowa Dekranasda in Bontolempangan and how the effectiveness of empowering persons with disabilities in the Bontolempangan sub-district, Gowa Regency. The research was conducted with qualitative methods, data collection was carried out by interviewing and selecting informants with. Purposive sampling. The research location is in the Bontolempangan sub-district, Gowa district. The results showed that 1). The form of empowerment carried out by the Gowa Dekranasda is by providing assistance to persons with disabilities in the form of production equipment. 2). The empowerment carried out for people with disabilities is bamboo crafts and sewing.